Marking Stress ExPLICitly in Written English Fosters Rhythm in the Reader's Inner Voice. Issue 3 (29th July 2017) - Gross, Jennifer; Winegard, Bo; Plotkowski, Andrea R.
Abstract: Spoken English has a stress‐alternating rhythm that is not marked in its orthography. In two experiments, the authors evaluated whether stylistic alterations to print that marked stress pulses fostered the rendering of rhythm (experiment 1) and stress (experiment 2) during silent reading. In experiment 1, silent readers rated the helpfulness of the stylistic alterations appearing in the last line of poems. In experiment 2, silent readers rated the helpfulness of the stylistic alterations appearing in heteronyms embedded in prose. As predicted by linguistic theories, when the stylistic alterations mapped onto the rhythmic pulses of the poems, and the lexically stressed syllables of the heteronyms, silent readers rated these alterations as more helpful compared with the incongruous conditions. In experiment 2, readers' inner voices were more tuned to the prosodic nuances of the first syllable than the second in the bisyllabic heteronyms. This prosodic tuning for the first syllable in a word was likely afforded by the strong tendency for stress to appear word‐initially. In addition, the stylistically marked stress was viewed as more helpful in the early half of the sentence, when readers likely recruited more bottom‐up processes. In both experiments, prior exposure to poetry was related to a refined prosodic awareness. In experiment 2, exposure to poetry predicted participants' prosody sensitivity, after controlling for the other predictors of academic achievement. The authors' ongoing studies are evaluating whether marking stress explicitly in written English might aid struggling readers and late speakers of English.